Effect of Feeding Rice based Distillers Dried Grains with Solubles without or with Different Enzymes on Carcass Characteristics in Broiler Chickens - Dinani, O. P.; Tyagi, Pramod K.; Mandal, A. B.; Tyagi, Praveen K.; Tiwari, S. P. (International Journal of Bio-resource and Stress Management, 2018)
A biological experiment was conducted to evaluate the effect of feeding rice based distillers dried grains with solubles (rDDGS) as soybean replacement without or with different enzymes on carcass characteristics in broiler chickens. The experiment was conducted as per 3x4 factorial completely randomized design. A total of 384 broiler chicks of same hatch with uniform weight were used. There were twelve different treatments with 4 replicates for each treatment and each replicate consisted of 8 chicks. Two levels of rice DDGS were taken (12.5 and 15%). Protease, xylanase and multienzymes supplementation under different treatments were done. The results revealed that no significant (p>0.05) difference was observed due to different levels of rice DDGS and their interaction with different enzymes in carcass traits, cut up parts, visceral organ and immune organ weight except abdomen fat and giblet weight. Abdomen fat was significantly (p<0.05) higher in 15% rDDGS level with or without xylanase supplementation. Xylanase supplementation increased significantly (p<0.05) giblet weight as compared to multienzymes and without enzyme groups. The study concludes that the feeding of rDDGS levels of 12.5% and 15%, respectively with or without enzyme supplementation do not have any adverse effects on the carcass traits, but xylanase supplementation improved abdomen fat and giblet weight of broiler chicken at 42 days.